A inclusão social pela participação em um projeto esportivo de caráter social : uma avaliação a partir da perspectiva de seus egressos - Aragão, Júlia Bigossi (2018)
A survey published by the Brazilian Institute of Geography and Statistics (IBGE, 2012) reveals the existence of 25,000 sports-recreational organizations throughout the country (9.6% of the total number of private foundations and active non-profit associations). It seems reasonable to consider that one of these projects is aimed at promoting social inclusion. In this research, we chose to work with the social inclusion approach defined by Donnelly (1996, apud BAILEY, 2005), which divides inclusion into four procedural categories: Spatial, Relational, Functional and Power. In view of the absence of conclusive empirical evidence on the effects of sport and physical education on social inclusion, the general objective of the research was to investigate the effects of social inclusion on participation in a social sport project (PECS) from the perspective of their graduates in light of the procedural categories of social inclusion. The present work is configured as an ex-post facto research, of analytical-descriptive type that uses qualitative-quantitative methods of inquiry in the form of opinion. The sample adopted is non-probabilistic of a voluntary type. From the data obtained it was not possible to state that the students improved economically due to their participation in the project, but with regard to the aspect of interpersonal relationships, we concluded that participation in the social project studied helped to improve or increase the level of acceptance or membership of a network of persons. As well as they were positive, reinforcing some previous researches that the participation in these projects amplifies the specific and general knowledge of the individual, as well as their abilities, since it is a space for learning. The last concept for inclusion did not have the same positive outlook in our project. As the "Tennis for All" follows almost independent of the local community, doing nothing together except for the participation of the children and youth in the project, as well as the children and young people do not build community activities or actions within it, inclusion as form of social empowerment is lost in the "Tennis for Everyone", since the students only receive what was offered.